Comparatif monitoring arthropod: Auxiliary-pest complex in vineyard table grapes cultivars in Boumerdes vineyards, Northern Algeria - Bissaad, Fatma Zohra; Marniche, Faiza; Bounaceur, Farid; Benmokhtar, Roumaissa (Future Science, 2025)
As an alternative to chemical treatments, traps are one of the most environmentally friendly ways to control pests in agricul-tural systems. The efficacy of traps can be maximized by taking adventage of the fact that arthropods, and especially pests, have preferences for certain colors and stimuli. From January to De-cember 2022, in the locality of Corso, situated in Boumerdes Province, Northern Algeria. The experimental site consisted of a three-year-old table grape plantation. A descriptive observa-tional method was employed to assess the performance of four different trap types: pitfall traps, food-based traps, and two col-or-based traps (yellow and blue). The experiment followed a completely randomized design with five replications to ensure reliable and accurate results. Yellow traps proved to be the most successful throughout the research., capturing a total of 1,925 arthropod individuals. In contrast, food-based traps were the least effective, with only 14 individuals captured. The traps re-vealed a richness of 106 species spanning 54 families, 11 orders, and 3 classes, highlighting the diverse arthropod community present in the vineyard ecosystem. The most frequently captured species was Jacobiasca lybica, which accounted for 81.6% of the total pests trapped. The timing of trap installation was also a crit-ical factor, with the morning period yielding the highest capture rates. These findings underscore the importance of using color-specific traps and strategic timing to enhance pest management in vineyards.